Flexural strengths of reinforced denture base resins subjected to long-term water immersion - Kaneyoshi Yoshida; Yutaka Takahashi; Hirono Sasaki; Ippei Hamanaka; Tomohiro Kawaguchi (Medical Journals Sweden, 2016)
Objective This study evaluated the flexural strengths of reinforced denture base resins subjected to long-term water immersion. Materials and methods Acrylic denture base resin reinforced with metal wire or glass fiber-reinforced composite (FRC), and without reinforcement were tested. Bar-shaped specimens were fabricated. Half of the specimens were stored in 37 °C distilled water for 50 hours (h), the other half were stored in 37 °C distilled water for 180 days (d) before testing. Ten specimens were fabricated per group for each reinforcement/water immersion period combination. The ultimate flexural strength and flexural strength at the proportional limit of reinforced denture base resin were tested. Results The 180 d bulk specimen possessed significantly lower ultimate flexural strength compared with the 50 h bulk specimen (p < 0.05). The ultimate flexural strength of the 50 h metal, 50 h FRC, 180 d metal and the 180 d FRC reinforcement specimens were not significantly different from each other (p > 0.05). The 180 d bulk specimen had a significantly lower flexural strength at the proportional limit compared to the 50 h bulk specimen. The 180 d reinforced specimens of metal and FRC were not significantly different from each of the 50 h specimens. Conclusion The flexural strengths of a reinforced denture base resin did not change after long-term water immersion.